2007
DOI: 10.1007/s10633-007-9067-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and multifocal-electroretinographic findings of congenital tilted disc syndrome associated with choroidal neovascularization: a case report

Abstract: Macular serous retinal detachment due to subretinal leakage is a rare complication of tilted disc syndrome. To the author's knowledge, this is the first time a tilted disc syndrome with choroidal neovascularization is documented by means of OCT and mf-ERG. These are the only objective tools in order to assess objectively the anatomical and functional damage accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A PubMed search using keywords 'tilted disc' and 'optical coherence tomography (OCT)' on 2 October 2012 extracted 13 articles. However, after excluding the myopic disc tilt, only seven studies examined TDS by OCT. [8][9][10][11][12][13][14] The purpose of OCT examination in six of these studies was limited to measuring the thickness of the peripapillary retinal nerve fiber layer or to analyzing the macular pathologies, for example, serous retinal detachment and choroidal neovascularization. It was not possible to observe the deeper structures within the optic nerve or the deeper tissues of the eye by conventional OCT.…”
Section: Introductionmentioning
confidence: 99%
“…A PubMed search using keywords 'tilted disc' and 'optical coherence tomography (OCT)' on 2 October 2012 extracted 13 articles. However, after excluding the myopic disc tilt, only seven studies examined TDS by OCT. [8][9][10][11][12][13][14] The purpose of OCT examination in six of these studies was limited to measuring the thickness of the peripapillary retinal nerve fiber layer or to analyzing the macular pathologies, for example, serous retinal detachment and choroidal neovascularization. It was not possible to observe the deeper structures within the optic nerve or the deeper tissues of the eye by conventional OCT.…”
Section: Introductionmentioning
confidence: 99%
“…Other ophthalmic changes can resemble myopia, myopic astigmatism, peripapillary atrophy (scleral or myopic crescent), inferior nasal thinning of the retinal pigment epithelium and choroid, posterior staphyloma or coloboma and superotemporal or bitemporal visual field defects [3]. In uncomplicated cases where there is no secondary chorioretinal neovascularisation [4] or serous macular detachment [5], the ophthalmoscopic appearance of the macula is normal apart from asymptomatic pigmentary changes described in about 11% of cases [5]. Recently Moschos et al [6] demonstrated reduced outer retinal function in the macula as measured with the multifocal electroretinogram (mfERG).…”
Section: Introductionmentioning
confidence: 99%